Dinámica poblacional y control químico de hydrellia wirthi korytkowski en oryza sativa l. var. ir – 43 en la calera – Guadalupe – La Libertad - Quesquen Medina, Anait Aracelly (2016)
The objective of this research was to describe the population dynamics and chemical control of Hydrellia wirthi Korytkowski in Oryza sativa L. var. IR - 43 in La Calera - Guadeloupe - La Libertad. For the study of population dynamics was evaluated weekly, 10 rice plants randomly chosen per sector and number of mined leaves, leaf number of mines and mine number of larvae was determined. The managed sectors were sector A, B, C, D, E. to which they were applied in the seedbed insecticides such as Imidacloprid (Fortagen 350 SC) dose of 5.12 ml /20 liters of water, and Lambda-cyhalotrín (Detoque) 12.5 ml/20 liters of water; in transplantation: Clothianidin (Dantotsu 50 WG) at doses of 150 g/Cil, and Dinotefuran (Stricto) with doses of 100 gr /Cil. It is noted that both the seedbed and transplant could obtain good control of Hydrellia wirthi Korytkowski. According to the results Hydrellia wirthi Korytkowski cause major attacks at the time of transplant.